2020
DOI: 10.26434/chemrxiv.12818174.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Catalytic Mechanics of Dynamic Surfaces: Stimulating Methods for Promoting Catalytic Resonance

Abstract: Transformational catalytic performance in rate and selectivity is obtainable through catalysts that change on the time scale of catalytic turnover frequency. In this work, dynamic catalysts are defined in the context and history of forced and passive dynamic chemical systems, with classification of unique catalyst behaviors based on temporally-relevant linear scaling parameters. The conditions leading to catalytic rate and selectivity enhancement are described as modifying the local electronic or steric enviro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…The blocking of the V S @1Fe-S50 site by H might play a role in the low NRR selectivity of Fedoped MoS 2 catalysts at large cathodic potentials reported in recent experiments. 22,29,30 Based on our results, it seems possible that NRR, using Fe-doped MoS 2 catalysts, may benefit from potential cycling approaches 61,62 to selectively favor N 2 adsorption at low potentials and, thereafter, drive the reduction of *N 2 at higher potentials. 3.5.1.1.…”
Section: H-mediatedmentioning
confidence: 79%
“…The blocking of the V S @1Fe-S50 site by H might play a role in the low NRR selectivity of Fedoped MoS 2 catalysts at large cathodic potentials reported in recent experiments. 22,29,30 Based on our results, it seems possible that NRR, using Fe-doped MoS 2 catalysts, may benefit from potential cycling approaches 61,62 to selectively favor N 2 adsorption at low potentials and, thereafter, drive the reduction of *N 2 at higher potentials. 3.5.1.1.…”
Section: H-mediatedmentioning
confidence: 79%
“…The dynamic strain results in a periodic conversion differing from equilibrium, consistent with other dynamic ratcheted systems. (21,57) In Figure 6A, the ammonia synthesis reaction was simulated in a batch reactor at 320 ⁰C and 20 atm starting with a stoichiometric mixture of H 2 and N 2 gases. Initial static catalysis proceeds to 33% conversion at equilibrium, after which dynamic strain (± 4%) at varying frequency (5, 10, 15, and 20 kHz) was imposed.…”
Section: Resultsmentioning
confidence: 99%
“…As recently described via simulation, (19,20) oscillation of the catalyst electronic state between sides of the Sabatier peak can accelerate the overall reaction rate, control the extent of reaction, and even select specific reaction pathways in a reaction network. (21,22) These dynamic catalysts exhibit a band of resonant applied frequencies yielding the highest catalytic turnover frequency unique to each catalytic reaction. Dynamic catalytic rate acceleration has already been demonstrated with dynamic formic acid electro-oxidation(23) and dynamic photocatalysis for methanol decomposition.…”
mentioning
confidence: 99%
“…It was further predicted that oscillations need to be in approximate resonance with the surface reactions to achieve reaction enhancements. [9][10][11][12] DFT calculations by Shetty et al revealed electric field-dependent linear scaling relationships of adsorbates on metal surfaces imperative for the understanding of dynamic catalytic processes. 13 Cycling between a potential suitable for the non-Faradaic dehydration of FA to surfaceadsorbed CO and the Faradaic oxidative desorption to form CO 2 enhanced the activity by a factor of up to around 20 at frequencies of 100 Hz, 14 consistent with promotional effect observed by Adžić et al earlier.…”
Section: Introductionmentioning
confidence: 99%